1998
DOI: 10.1159/000026522
|View full text |Cite
|
Sign up to set email alerts
|

Upregulation of the Platelet Serotonin<sub>2A</sub> Receptor and Low Blood Serotonin in Suicidal Psychiatric Patients

Abstract: Suicidality has been found to be associated with low pre- and postsynaptic serotonin functioning. The purpose of this study was to examine whether in acutely suicidal psychiatric inpatients, the blood serotonin concentration was related to the underlying psychiatric disorder and whether it was associated with changes in the affinity (dissociation constant, KD) or in the maximal binding capacity (Bmax) of the platelet serotonin2A receptor. We therefore determined the blood serot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
30
0
1

Year Published

2000
2000
2010
2010

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(33 citation statements)
references
References 34 publications
2
30
0
1
Order By: Relevance
“…For example, some studies of 5-HT 2A receptors in platelets have found significant elevations (Pandey et al, 1990(Pandey et al, , 1995Hrdina et al, 1995Hrdina et al, , 1997Rao et al, 1998;Alda and Hrdina, 2000), while others have not (McBride et al, 1994;Neuger et al, 1999;Rosel et al, 1999). Similar results have been shown in post-mortem brain specimens from depressed patients; in some studies, apparent 5-HT 2A binding was elevated (Stanley and Mann 1983;Mann et al, 1986;Hrdina et al, 1993;Arranz et al, 1994;Pandey et al, 2002a, b), but not in others (Cheetham et al, 1988;Rosel and Arranz, 1998;Gross-Isseroff et al, 1998;Rosel et al, 2000).…”
Section: Introductionmentioning
confidence: 76%
“…For example, some studies of 5-HT 2A receptors in platelets have found significant elevations (Pandey et al, 1990(Pandey et al, , 1995Hrdina et al, 1995Hrdina et al, , 1997Rao et al, 1998;Alda and Hrdina, 2000), while others have not (McBride et al, 1994;Neuger et al, 1999;Rosel et al, 1999). Similar results have been shown in post-mortem brain specimens from depressed patients; in some studies, apparent 5-HT 2A binding was elevated (Stanley and Mann 1983;Mann et al, 1986;Hrdina et al, 1993;Arranz et al, 1994;Pandey et al, 2002a, b), but not in others (Cheetham et al, 1988;Rosel and Arranz, 1998;Gross-Isseroff et al, 1998;Rosel et al, 2000).…”
Section: Introductionmentioning
confidence: 76%
“…108 The importance of 5-HT2A receptor upregulation as marker for suicidality was further underlined by a recent investigation showing that in suicide brains the lifetime aggression scores correlated positively with 3 H-ketanserin binding in all investigated prefrontal Brodman areas. 109 Further, several studies with platelets of suicide attempters showed an upregulation of 5-HT2A receptor as a peripheral marker for suicidality, 110,111 although a critical review claimed that methodological flaws limited the validity of platelets as biological model.…”
Section: Serotonin Receptorsmentioning
confidence: 99%
“…The direction of findings in the brain of suicides is consistent with some platelet findings in suicide attempters. For example, more platelet 5-HT 2A receptors are found in suicide attempters compared with non-attempters and healthy controls (Arora and Meltzer, 1993 ;Biegon et al, 1990 ;McBride et al, 1994 ;Pandey et al, 1990Pandey et al, , 1995Rao et al, 1998), and in individuals with suicidal ideation compared to non-suicidal psychiatric patients and controls (Alda and Hrdina, 2000 ;Bakish et al, 1997 ;Hrdina et al, 1997). Two studies observed no difference (Serres et al, 1999 ;Uchitomi et al, 2002).…”
Section: Introductionmentioning
confidence: 98%